2017
DOI: 10.1021/acs.bioconjchem.7b00075
|View full text |Cite
|
Sign up to set email alerts
|

Coating Nanoparticles with Plant-Produced Transferrin–Hydrophobin Fusion Protein Enhances Their Uptake in Cancer Cells

Abstract: The encapsulation of drugs to nanoparticles may offer a solution for targeted delivery. Here, we set out to engineer a self-assembling targeting ligand by combining the functional properties of human transferrin and fungal hydrophobins in a single fusion protein. We showed that human transferrin can be expressed in Nicotiana benthamiana plants as a fusion with Trichoderma reesei hydrophobins HFBI, HFBII, or HFBIV. Transferrin-HFBIV was further expressed in tobacco BY-2 suspension cells. Both partners of the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
0
17
1
1
Order By: Relevance
“…For example, Tf has been widely explored as a targeting ligand for improving BBB penetration of nanocarriers such as micelles 46 , liposomes 47 , and polymersomes 48 . Coating of Tf on pSiNP through hydrophobic interactions was first described by Reuter et al 49 They observed that Tf modification enhanced the internalisation into breast cancer cells. In this work, we studied whether Tf conjugation on pSiNP surface could enhance the internalisation into GBM cancer cells.…”
Section: Discussionmentioning
confidence: 94%
“…For example, Tf has been widely explored as a targeting ligand for improving BBB penetration of nanocarriers such as micelles 46 , liposomes 47 , and polymersomes 48 . Coating of Tf on pSiNP through hydrophobic interactions was first described by Reuter et al 49 They observed that Tf modification enhanced the internalisation into breast cancer cells. In this work, we studied whether Tf conjugation on pSiNP surface could enhance the internalisation into GBM cancer cells.…”
Section: Discussionmentioning
confidence: 94%
“…Rapid accumulation of biomass and easy transformation has made the BY-2 cells the most frequently used plant cell line for protein production ( Doran, 2013 ). Proteins ranging from antibodies, enzymes, and therapeutic to technical proteins ( Sakamoto et al, 2008 ; Kirchhoff et al, 2012 ; Reuter et al, 2017 ) have been successfully expressed in BY-2 cells. However, when it comes to industrial production, two factors must be specifically ensured: stability of the production host and the cost efficiency of the production process ( Kurppa et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, size, shape, size distribution and zeta potential of colloidal nanoparticles can affect their fate after systemic injection, and modulate distributions through passive targeting. 19 22 Furthermore, surface properties, 23 25 and modifications, 26 28 of colloidal nanoparticles can affect their potentialities in therapy, control pharmacokinetic and biodistribution, and target selectively cells and tissues.…”
Section: Resultsmentioning
confidence: 99%